RENAL REBIOPSY IN LUPUS NEPHRITIS: EXPERIENCE OF A TERTIARY HOSPITAL - Valéria Marques da Silva; Stefanie Queiroz Brito; Jhonatan Costa Messias; Renata Ferreira Rosa; Nafice Costa Araújo (2023)
BACKGROUNDRenal involvement is the leading cause of morbidity and mortality in patients with systemic lupus erythematosus (SLE), with biopsy as the gold standard for diagnosis.According to Eular 2019, we use the classification of the International Society of Nephrology/ Renal Pathology Society 2003 to classify biopsy findings compatible with lupus nephritis.Treatment is based on an induction phase and a maintenance phase.In cases of recurrence, studies show uncertain benefits of a new renal biopsy.This study was conducted to report the experience of a tertiary hospital in performing the second renal biopsy in lupus patients with renal recurrence.